Detecting amyloid positivity in early Alzheimer's disease using combinations of plasma Aβ42/Aβ40 and p‐tau. Issue 2 (20th June 2021) - Janelidze, Shorena; Palmqvist, Sebastian; Leuzy, Antoine; Stomrud, Erik; Verberk, Inge M.W.; Zetterberg, Henrik; Ashton, Nicholas J.; Pesini, Pedro; Sarasa, Leticia; Allué, José Antonio; Teunissen, Charlotte E.; Dage, Jeffrey L.; et al.
Abstract: Introduction: We studied usefulness of combining blood amyloid beta (Aβ)42/Aβ40, phosphorylated tau (p‐tau)217, and neurofilament light (NfL) to detect abnormal brain Aβ deposition in different stages of early Alzheimer's disease (AD). Methods: Plasma biomarkers were measured using mass spectrometry (Aβ42/Aβ40) and immunoassays (p‐tau217 and NfL) in cognitively unimpaired individuals (CU, N = 591) and patients with mild cognitive impairment (MCI, N = 304) from two independent cohorts (BioFINDER‐1, BioFINDER‐2). Results: In CU, a combination of plasma Aβ42/Aβ40 and p‐tau217 detected abnormal brain Aβ status with area under the curve (AUC) of 0.83 to 0.86. In MCI, the models including p‐tau217 alone or Aβ42/Aβ40 and p‐tau217 had similar AUCs (0.86–0.88); however, the latter showed improved model fit. The models were implemented in an online application providing individualized risk assessments (https://brainapps.shinyapps.io/PredictABplasma/ ). Discussion: A combination of plasma Aβ42/Aβ40 and p‐tau217 discriminated Aβ status with relatively high accuracy, whereas p‐tau217 showed strongest associations with Aβ pathology in MCI but not in CU.